SOSIALISASI PENGELOLAAN DAN PENGAMANAN AKUN MEDIA SOSIAL KEPADA MASYARAKAT - Arezou Ghoyah Arridwan Syafii; Sandi Maulana; Rafi Naufal R; Trisna Nur Andika; Ito Setiawan (JURNAL ILMIAH NUSANTARA, 2026)
The rapid development of information technology has significantly increased the number of social media users, yet this trend is not always accompanied by adequate digital literacy, particularly among adults and the elderly. This lack of understanding results in a high risk of cyberattacks and personal data misuse. This community service activity aims to enhance the understanding and skills of PKK members (Family Welfare Movement) in managing and securing social media accounts. The methods employed were educational and participatory, involving material presentations, interactive discussions, and direct demonstrations, including the introduction of parental control features. The results of this activity indicate an increase in participants' awareness regarding the importance of data security, the ability to identify hoaxes, and social media ethics. This socialization is expected to foster a safer and more responsible digital environment at both family and community levels.